DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN MENULIS TEKS CERITA PENDEK DI KELAS 7 SMPN I LURAGUNG - Elin Linawati (Jurusan Tadris Bahasa Indonesia, 2016)
This study aims to improve students' skills in writing short stories. Discovery learning can improve students' ability to generate stories. This study uses a Class Action Research (PTK). The results are as follows. In prasiklus use the lecture method with media Charta with KKM 75. In the aspect of knowledge is only 55% of students who completed and only 66% skill aspect. The results of the first cycle of learning by using discovery learning strategies in preparing the text of the short story nilail obtain an overall average of 76. In the knowledge that acquired skill aspect nilail overall average of 77. Although it has exceeded KKM, but have not reached the targets set in the classical style, ie 80. The observation of posture is 2.88. Activities teachers earned an average of 3.11. Weakness in the first cycle is fixed in the second cycle, both related to the design of learning, learning, and assessment. In the second cycle, student achievement related knowledge reached an average of 79.16. Students who have completed a total of 36 people (100%). Aspects acquire skills nilail overall average, that student attitudes 81. Observations 3.21. Results of teacher activity observation was 3.47 including both categories.